Sistem Pendukung Keputusan Dalam Kelayakan Penerima Bantuan PKH Menggunakan Metode Multi Objective Optimization On The Basic Of Rat Io Analysis (MOORA) - Widia Sari; Herlina Latipa Sari; Jhoanne Fredricka (Jurnal Media Infotama, 2025)
The Family Hope Program (PKH) is one of the government's efforts to overcome poverty by providing social assistance to poor families. However, selecting the right and objective recipients of assistance is an important challenge to ensure that the assistance is right on target. This study aims to develop a decision support system (DSS) in determining the eligibility of PKH assistance recipients using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. The MOORA method was chosen because of its ability to process several criteria simultaneously, So that it can provide more accurate and objective decisions. The system considers various criteria such as income level, number of family members, and socio-economic status to calculate the eligibility score of aid recipients. The results of this system are expected to provide recommendations for PKH aid recipients that are more efficient, fair, and in line with government priorities. The trials conducted on aid recipient data are expected to demonstrate the accuracy and effectiveness of the system in facilitating more precise and transparent decision-making.